G166(P) Extreme PRTETRM babies with complex congenital heart diseases. (27th April 2016) - Abdulla, Y; Pattnayak, S; McElroy, H; Soe, A
Abstract : Introduction: Survival of extreme preterm babies born between 22–25 weeks of gestation and their disability free survival have increased from 1995 to 2006 in England; however neonatal morbidity has not changed significantly. There is paucity of information about the outcome of these babies in presence of complex congenital heart disease (CHD). Aim of the study: To find out the prevalence of complex CHD in babies born in this hospital with a gestational age from 22+0 -25+6 weeks during 01 Apr 2008 to 31 Mar 2015 and also to determine their survival, short and long term outcomes. Method: Total number of live births, total neonatal admissions, number of extreme preterm admissions including in-utero and ex-utero transfers were collected from maternity (Euro king) and neonatal database (Badgernet). The cases of complex CHD were identified from Badgernet and verified from Unit admission register. Cases with PFO, PDA and VSD were excluded. The identified cases were reviewed for survival, oxygen dependency at 36 weeks (CLD), Retinopathy of prematurity (ROP), necrotising enterocolitis (NEC) and neurodevelopmental (ND) outcome at 2 years of age. Results: Total live births: 34307, total neonatal admissions: 6028, number of admissions for babies <25+6 weeks: 181 (Inborn: 92, ex-utero transfers: 89), complex CHD in inborn group were 2. Conclusion: This is a single centre experience of complex CHD in this high risk group. A multicentre collaborative study will help providing valuable information on their outcome.